Penyuluhan Pemberdayaan Masyarakat Tentang Pemilihan Makanan Sehat Junk Food VS Healty Food - Dwi Ris Hasanah S; Nurdiana Manurung (Journal of Community Development, 2023)
Diet is an important behavioral pattern that affects the health of a person or group. In Dusun IV of Hamparan Perak Village, awareness of the importance of a healthy diet, especially among children, was raised through counseling activities on junk food. With a focus on the frequency of consumption and factors that influence its choice, parents and children were taught to understand the difference between healthy food and junk food.Through the counseling method, information is delivered in a way that is easily understood by children and parents. As a result, they became more aware of the negative impacts of junk food consumption and the importance of making healthy food choices. With a better understanding of food choices, it is hoped that children and parents can make better decisions in their diet, leading to better health and preventing the risk of diseases related to unhealthy diets. This activity is the first step in creating a healthier eating culture in Dusun IV Hamparan Perak Village, strengthening awareness of the importance of proper nutrition for children's growth and development.